ANALISIS KEBERLANJUTAN PADA ASPEK EKOLOGI TERHADAP KEGIATAN HUTAN RAKYAT POLA AGROFORESTRY DI KABUPATEN KERINCI: Sustainable Analysis on The Ecological Aspect in The Agroforestry Pattern in Kerinci District - Rahmad Nurmansah; Hamzah Hamzah; Edison Edison (Jurnal Silva Tropika, 2021)
The existence of community forests provides many benefits both ecologically and economically for the community, so that it can create sustainable community forest development. Community forest consists of various types of systems or one of them is a model of agroforestry community forest system. Public forest agroforestry patterns have the function of being able to maintain food production, especially by slowing down nutrient and energy losses, and resisting the destructive power of water, wind, floods and landslides and can increase economic income. The purpose of this study was to look at the income of community forest farming agroforestry patterns and to see the sustainable status of community forests in agroforestry patterns. The income analysis used by using the equation of farming and sustainable income analysis using the Multi Dimensional Scaling (MDS) approach with the Rap-Pforest (Rapid Appraisal for Private-Forest) program. The results of community forest activities using agroforestry patterns that the results of the analysis of the sustainable status of community forest activities with agroforestry patterns Sustainability in ecological aspects show the number 79.67 (Sustainable)